2014
DOI: 10.1080/00221309.2014.897215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Maternal Separation on Subsequent Reproductive and Behavioral Outcomes in Male Rats

Abstract: To investigate effects of maternal separation on reproductive and behavioral outcomes, male Wistar rats were separated from their mothers daily for 3 hr (maternal separation; MS) or 0 hr (control) from postnatal day (PND) 1 to 14. Timing of puberty, reproductive parameters, hormone levels, and aggressive behaviors in juvenile and adult rats were examined. Contrary to expectations, there was no effect of maternal separation on any measure of aggression. However, maternal separation altered peripubertal testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
4
17
2
Order By: Relevance
“…During puberty, testosterone has been shown to promote IL-10 expression in males (Zhang et al, 2007); therefore the observed drop in IL-10 in MS males during puberty suggests that the reduced testosterone reported here, and observed by others (Bodensteiner et al, 2014), in adolescent MS males could have a modulatory role of IL-10 levels in these rats. Notably, we did not observe an effect of MS on the timing of puberty in males as measured by balano-preputial separation; therefore it does not appear that decreased testosterone levels affected the timing of pubertal development.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…During puberty, testosterone has been shown to promote IL-10 expression in males (Zhang et al, 2007); therefore the observed drop in IL-10 in MS males during puberty suggests that the reduced testosterone reported here, and observed by others (Bodensteiner et al, 2014), in adolescent MS males could have a modulatory role of IL-10 levels in these rats. Notably, we did not observe an effect of MS on the timing of puberty in males as measured by balano-preputial separation; therefore it does not appear that decreased testosterone levels affected the timing of pubertal development.…”
Section: Discussionsupporting
confidence: 69%
“…Since MS has not been shown to affect baseline estradiol levels in female rats but can alter peripubertal testosterone secretion (Bodensteiner et al, 2014), we also assessed plasma testosterone concentrations from blood samples at P35 using ELISA (R&D, Minneapolis, US). The mean minimum detectable dose was 0.030 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Bodensteiner et al (2014) have recently shown that MS males displayed a delay in puberty and decreased testosterone levels on PND 42. As adults, MS males have been shown to display a lower number of sexual behaviors, despite the observation of similar levels of testosterone in MS and control rats (Bodensteiner et al, 2014). Therefore, we cannot rule out the possibility that MS‐induced changes in peri‐ or postpubertal levels of sex hormones are also responsible for the sex‐related differences in our study.…”
Section: Discussionmentioning
confidence: 98%
“…However, during puberty testosterone has been shown to promote an anti‐inflammatory profile in males (Zhang, Xing, He, & Wang, ); therefore, the observed pro‐inflammatory profile in MS‐exposed adolescent males suggests that testosterone modulation of cytokines may be diminished in these rats. Indeed, adolescent male rats exposed to MS have been shown to display reduced testosterone levels (Bodensteiner, Christianson, Siltumens, & Krzykowski, ). Although we did not assess gonadal hormones in the present study, the differential influence of hypothalamic–pituitary–gonadal axis development on immune function in males and females may contribute to sex‐dependent effects of MS and requires further study.…”
Section: Discussionmentioning
confidence: 99%